Bibliotecário clínico: análise do perfil de um profissional dinâmico - Mariana Ribeiro Fernandes (2015)
The research aimed to analyze the profile and skills of the clinical librarian who works in Brazilian hospitals in the Medical process Based evidenced MBE. This medical practice came up with the definition of careful and conscious use of the best available scientific evidence, to make decisions concerning the care of patients. The Clinical Librarian, so called in the United States and other countries is part of the link in the EBM and the clinical staff make up the key elements of the process of improving the quality of medical care and making health decision. Empirical research was conducted with 31 University Hospitals of Southeast over the Sahara Kubischek Hospital in Brasilia-DF out to be one of the first hospitals to rely on librarian on your team. The questionnaire was used to collect data to gather information about the work of librarians in hospitals detected. The same was divided into four blocks, professional profile, professional practice, communication with peers and evidence-based medicine, which was used as a data analysis tool. First identified the existence of these hospitals Librarian and subsequently analyzing the research subjects in accordance with the scenario existing in the outside. The main results indicate that there is clinical librarians working in Brazil, and who perform tasks involving the Evidence Based Medicine in order to assist in the search for information in hospitals, participating in meetings with the clinical staff in the decision-making process. Even if "clinical librarians" happen in an unusual way in Brazil these professionals have a profile a bit far from the reality existing outside, but with the path to be similar.